PENGARUH SERAT WARU (Hibiscus Tiliaceus) TERHADAP KARAKTERISTIK MORTAR GEOPOLIMER BATU NAPAL - Vike Itteridi; Edowinsyah; Dimas Rusdianto (Jurnal Ilmiah BERING, 2023)
This study discusses the addition of hibiscus fiber to the characteristics of marl geopolymer mortar. Geopolymer Mortar is a mortar with a binder that completely does not use cement as a binder. The research method used was alkaline activator NaOH and Na2SiO3 with a ratio of 1: 1 and a molarity of 16 M. The percentage of fiber addition used was 0%, 0.5% and 1.5% of the weight of the precursor and the length of the fiber was 2 cm. All specimens were tested for compressive strength at the age of 3, 7, 14, 21 and 28 days. The results of the research that have been carried out, it was found that the compressive strength at the age of 28 days with 0% fiber proportion was 3.07 Mpa. Meanwhile, the proportion of 0.5% fiber is 2.53 MPa and the proportion of 1.5% fiber is 2.27 MPa